Evaluation of WC-10Ni thermal spray coating with shot peening on the fatigue strength of AISI 4340 steel - Junior, G. S. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Vieira, L. F. S. [UNESP]; Cioffi, M. O. H. [UNESP]; Bonora, R. G. [UNESP] (Elsevier B.V., 2010)
Fatigue failure is a result of a crack initiation and propagation, in consequence of a cyclical load. In aeronautical components as landing gear the fatigue strength is an important parameter to be considered in project, as well as the corrosion and wear resistance.The thermal sprayed HVOF technology it's normally used to protect components against wear and corrosion, and are being considerate an alternative to replace chromium by the aeronautical industry. With respect to fatigue life, the HVOF technique induces residual stress on the interface. In the case of tensile residual stresses, the initiation and propagation phases of fatigue process are accelerated; on the other hand, compressive residual stresses close to the surface may increase fatigue life. The technique to improve the coated materials fatigue strength is the shot peening process, which induces residual stress in the surface in order to delay the nucleation and propagation process.The aim of present study is to compare the influence of WC-10 Ni coating applied by HVOF on the fatigue strength of AISI 4340 steel, with and without shot peening. S-N curves were obtained in axial fatigue tests for material base, and tungsten carbide coated specimens. (C) 2010 Published by Elsevier Ltd.
Keywords: Shot peening; Residual stress; 4340 Steel; Fatigue; HVOF process